Carbonation of filler typed self-compacting concrete and its impact on the microstructure by utilization of 100% CO2 accelerating techniques - Mohammed, Mahmoud khashaa; Dawson, Andrew; Thom, Nicholas (Elsevier, 2014)
Via the use of accelerated carbonation techniques with 100% CO2 concentration, an experimental programme was performed to investigate the carbonation and associated microstructural changes of three different self-compacting concrete (SCC) in which some of the cement had been replaced by limestone powder, fly ash and/or silica fume. Accelerated carbonation tests were conducted on these “filler-typed” SCCs after 28 days water curing. Approximately 33% of the total binder (450 kg/m3) was replaced by limestone powder, fly ash or a fly ash–silica fume blend.